2014
DOI: 10.1371/journal.pone.0115107
|View full text |Cite|
|
Sign up to set email alerts
|

Thrombospondin-1 Production Is Enhanced by Porphyromonas gingivalis Lipopolysaccharide in THP-1 Cells

Abstract: Periodontitis is a chronic inflammatory disease caused by gram-negative anaerobic bacteria. Monocytes and macrophages stimulated by periodontopathic bacteria induce inflammatory mediators that cause tooth-supporting structure destruction and alveolar bone resorption. In this study, using a DNA microarray, we identified the enhanced gene expression of thrombospondin-1 (TSP-1) in human monocytic cells stimulated by Porphyromonas gingivalis lipopolysaccharide (LPS). TSP-1 is a multifunctional extracellular matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…Moreover, bacterial components induce tenascin‐C expression in human monocyte‐derived and mouse bone‐marrow‐derived macrophages . Lipopolysaccharide from Porphyromonas gingivalis induces thrombospondin‐1 production in THP‐1 cells, while LPS from Escherichia coli and IFN‐ γ up‐regulate galectin‐1 and galectin‐3, including five galectin‐3 truncated forms, in primary human macrophages . In mice with viral myocarditis, macrophages infiltrating the heart are the main producers of osteopontin .…”
Section: Macrophages: Not Just Destroyers Of the Ecmmentioning
confidence: 99%
“…Moreover, bacterial components induce tenascin‐C expression in human monocyte‐derived and mouse bone‐marrow‐derived macrophages . Lipopolysaccharide from Porphyromonas gingivalis induces thrombospondin‐1 production in THP‐1 cells, while LPS from Escherichia coli and IFN‐ γ up‐regulate galectin‐1 and galectin‐3, including five galectin‐3 truncated forms, in primary human macrophages . In mice with viral myocarditis, macrophages infiltrating the heart are the main producers of osteopontin .…”
Section: Macrophages: Not Just Destroyers Of the Ecmmentioning
confidence: 99%
“…Thrombospondin‐1 (TSP‐1) has been associated with some systemic diseases, including RA (Rico et al , ; Ohyama et al , ) and DM (Choi et al , ; Wang et al , ). Gokyu et al () found that after THP‐1 cells were stimulated with LPS from Porphyromonas gingivalis , the gene expression of TSP‐1 was markedly elevated via the TLR2‐mediated NF‐ κ B pathway, indicating that TLR2 might be involved in TSP‐1 production that could exacerbate RA or DM. Based on this study, TLR2 has been suggested as a potential therapeutic target in the treatment of PD, RA, and DM.…”
Section: Tlrs In Cp With Systemic Diseasesmentioning
confidence: 99%
“…Zinc is sensitive to HNF4 [187] and reduced hepatic TNF-α toxicity [188,189] may aid the prevention of insulin resistance and AD [1]. Nutriproteomic diets as a treatment for reduction of LPS effects may lower TSP-1 expression by peripheral cells [190,191,192] and improve peripheral LPS–protein interactions [193,194,195,196] to accelerate peripheral amyloid beta metabolism with respect to treatment of individuals with prodromal disease and dementia. Nutritional diets that activate Sirt 1 and maintain therapeutic VIP and FGF21 levels [51] accelerate hepatic LPS/mycotoxin metabolism without transfer to the CSF and brain compartment [21], which is consistent with the use of nutritional therapy to maintain CSF composition, recycling, and amyloid beta dynamics [197,198] for the prevention of early neurodegeneration (stages 1–3) and amyloidosis.…”
Section: Nutriproteomic Diets Regulates Plasma Biomarkers and Revementioning
confidence: 99%